Pot Tanam Organik Sekam Padi dalam Rangka Mendukung Gerakan Revolusi Hijau di Kalimantan Selatan - Khairun Nisa; Noor Mirad Sari; Violet Violet (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The community partnership program for making organic planting pots aims to provide knowledge and technology on using waste from rice husks into eco-friendly organic planting pot products and train people in making these pots. Partners in the program are the Bina Desa Farmer Group in Pemangkih Village Tatah Makmur District Banjar Regency. The activity method is socialization/counseling, training, and assistance to partners. The community partnership program was implemented from May to September 2020 through meetings with the community partners who continue to apply the Covid-19 Protocol, resulting in organic planting pot products, publications in the mass media, video activities on YouTube, and scientific articles. Partners' knowledge increased between 76.47-94.12% after extension activities training on making organic planting pots.